Empidideicus jirofti sp. nov. (Diptera: Mythicomyiidae: Empidideicinae), a new microbombyliid from Kerman province, southern Iran, with a key to species of Empidideicus from Iran - Moghbeli, Sajjad; Fekrat, Lida; Gharali, Babak (Zootaxa, 2020)
A new species of the genus Empidideicus, E. jirofti Gharali, Mogbeli & Fekrat sp. nov., is described from the south of Iran, and diagnostic morphological and genitalic features are photographed. This species is distinguished by the completely dark brown occiput with yellow spot, completely dark brown scutellum, and dark brown mesonotum with two admedian yellow vittae. A key to the Iranian species of the genus is provided.